Failure protection in layered networks with shared risk link groups. - Dahai Xu (IEEE Network : the magazine of global information exchange)
The shared risk link group (SRLG) has been widely recognized as a fundamental concept in layered network design by the industry. However, several issues related to SRLG protections that are of both theoretical interest and practical importance have not been explored fully. Two major issues are avoiding failures caused by "traps" in finding backup paths, and minimizing the total network capacity requested by active and backup paths. In this article, we highlight the significance of the trap problem in layered networks with SRLG and evaluate the performance of several existing SRLG protection schemes in terms of trap avoidance and bandwidth efficiency, as well as their complexities. We also demonstrate that a simple yet intelligent heuristic algorithm can achieve good performance.